2020
DOI: 10.1093/pm/pnaa128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcranial Direct Current Stimulation on Chronic Neuropathic Pain in Patients with Multiple Sclerosis: Randomized Controlled Trial

Abstract: Objective Chronic neuropathic pain is a common symptom in multiple sclerosis (MS). This randomized controlled single-blinded study investigated whether a new protocol involving five days of transcranial direct current stimulation (tDCS) with an interval period would be effective to reduce pain using the visual analog scale (VAS). Other secondary outcomes included the Neuropathic Pain Scale (NPS), Depression Anxiety Stress Score (DASS), Short Form McGill Pain Questionnaire (SFMPQ), and Multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
23
0
2
Order By: Relevance
“…The analgesic mechanisms of rTMS and tDCS are similar, which both alter cortical excitability and synaptic plasticity, regulate the release of related neurotransmitters, and affect the structural and functional connections of brain regions associated with pain processing and regulation ( Figure 4 ; Zheng et al, 2011 ; Thibaut et al, 2017 ; Hassan et al, 2021 ; Molero-Chamizo et al, 2021 ). tDCS has been studied in several studies and was able to manage pain effectively, but its optimal stimulation targets, stimulation intensity, and stimulation time for each type of CNP are still difficult to identify ( Iodice et al, 2017 ; Wen et al, 2017 ; Young et al, 2020 ). NIBS not only affects the cerebral cortex at the stimulated site but also affects the related functional areas of the brain based on the pain matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic mechanisms of rTMS and tDCS are similar, which both alter cortical excitability and synaptic plasticity, regulate the release of related neurotransmitters, and affect the structural and functional connections of brain regions associated with pain processing and regulation ( Figure 4 ; Zheng et al, 2011 ; Thibaut et al, 2017 ; Hassan et al, 2021 ; Molero-Chamizo et al, 2021 ). tDCS has been studied in several studies and was able to manage pain effectively, but its optimal stimulation targets, stimulation intensity, and stimulation time for each type of CNP are still difficult to identify ( Iodice et al, 2017 ; Wen et al, 2017 ; Young et al, 2020 ). NIBS not only affects the cerebral cortex at the stimulated site but also affects the related functional areas of the brain based on the pain matrix.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is that the short follow-up period does not provide data to draw conclusions regarding the long-term efficacy of tDCS. Some studies conducted on younger populations showed that 5 sessions of tDCS can produce a significant hypoalgesic effect that can last up to 6 months after the end of stimulations ( 83 85 ). In older adults, the longest follow-up period for 5 tDCS sessions demonstrated that knee OA pain can be reduced up to 3 weeks after the last tDCS intervention ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Хімічна та/або електрична стимуляція, а також гальмування мозку та підшкірної клітковини використовували для лікування різних хронічних больових станів [47]. Транс краніальна стимуляція [48], стимуляція поля перифе ричних нервів, черезшкірна спінальна стимуляція [49] також на лежать до методів лікування НБ при РС.…”
Section: лікування нб при рсunclassified